2022
DOI: 10.3390/healthcare10081534
|View full text |Cite
|
Sign up to set email alerts
|

Proposing a Scientific and Technological Approach to the Summaries of Clinical Issues of Inpatient Elderly with Delirium: A Viewpoint

Abstract: Background/rationale: Despite mounting evidence about delirium, this complex geriatric syndrome is still not well managed in clinical contexts. The aging population creates a very demanding area for innovation and technology in healthcare. For instance, an outline of an aging-friendly healthcare environment and clear guidance for technology-supported improvements for people at delirium risk are lacking. Objective: We aimed to foster debate about the importance of technical support in optimizing healthcare prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The results highlighted the heterogeneous nature of knowledge within our sample, with no significant association with socio-demographic variables. Overall, the knowledge level was found to be inadequately aligned with the increasing clinical impact of delirium on healthcare services [ 5 , 15 ]. Similar levels of poor delirium knowledge have been reported in previous studies in China and the Netherlands [ 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results highlighted the heterogeneous nature of knowledge within our sample, with no significant association with socio-demographic variables. Overall, the knowledge level was found to be inadequately aligned with the increasing clinical impact of delirium on healthcare services [ 5 , 15 ]. Similar levels of poor delirium knowledge have been reported in previous studies in China and the Netherlands [ 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Delirium is a clinical and organizational issue involving the entire healthcare system that needs resource allocation and multidisciplinary research [ 5 ] and stands as the predominant complication observed among hospitalized individuals aged 65 years and older, impacting in excess of 2.6 million senior citizens annually within the United States [ 6 ]. Despite its notable prevalence, it frequently goes unnoticed, as demonstrated by a study by De La Cruz et al estimating the rate of undetected delirium to be as elevated as 60% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%